Writing and Rewriting Nationhood: "Henry V" and Political Appropriation of Shakespeare - Minami, Hikaru (Multicultural Shakespeare: Translation, Appropriation and Performance, 2023)
Shakespeare’s Henry V is often regarded as a nationalistic play and has been appropriated for political spin and propaganda to enhance the sense of national unity. Shakespeare captures the emerging nationalistic feeling of the Tudor era in Henry’s emphasis on national history and pride, but various parts of the text suggest a more diverse and complex figures of the king and his subjects than a war hero and the united nation. Such complexity, however, is often ignored in political appropriation. Laurence Olivier’s film adaptation during WWII glamorizes the war and defines the English nation as a courageous “band of brothers” through its presentation of Shakespeare’s play a shared story or history of national victory. Kenneth Branagh’s film in 1989, on the other hand, captures the ugliness of war but it still romanticizes the sacrifice for the country. In 2016, Shakespeare was made part of the Brexit discourse of growing nationalism at the time of the EU referendum. Brexit was imagined as a victory that will bring back freedom and sovereignty the country once enjoyed, and Shakespeare was used to represent the greatness of Britain. Shakespeare’s text, however, depicts the war against the continent in a more skeptical than glorifying tone. The war scenes are scattered with humorous dialogues and critical comments and the multi-national captains of Henry’s army are constantly at odds with one another. Shakespeare thus provides us with a wider view of nationhood, resisting the simplifying force of politics.